Building Structure Control System Application Research Based on Fuzzy Logic Algorithm - Ling Wang (IEEE Access, 2023)
With the development of society, the shortcomings of traditional building structure control methods have become increasingly apparent, including the inability to handle system uncertainty and nonlinear characteristics. To improve the control effect of building structure control, this study combines a fuzzy control algorithm and particle swarm optimization algorithm to obtain a hybrid algorithm and then combines the hybrid algorithm with a piezoelectric friction damping structure to design a new type of building structure control system. In the performance testing of the fuzzy control optimization model based on piezoelectric friction damping structure, the hysteresis curve area, isolation layer displacement, and damping rate of the isolation support under particle swarm fuzzy logic control were 12, 18.12cm, and 24%, respectively, which were superior to the comparative control method. Subsequently, further performance verification experiments were conducted on the proposed structural control system. The results showed that the peak inter-story displacement reduction rate of the structure under particle swarm optimization fuzzy logic control was 12.5%, and the acceleration of the isolation layer did not change significantly. The above results indicate a good control effect, effectively improving the stability and safety of building structures, which has great practical application value.